Refusal of Youth to Vote in Shah Alam, Selangor, Malaysia - Ramlan Mohd Arshad, Mohd; Mohd Salleh, Norhayati; ., . (International Journal of Engineering and Technology, 2018)
The involvement of youth in todayâ€™s politic will influence the future state of Malaysia. The aim of this research is to study on the antecedents that make youth refuse to vote in Shah Alam. The respondents for this research are the youth whom registered as voter for Shah Alam Parliamentary seat. The main objective of this study is to determine the most significance factor that affected their voting behavior. The respondent of this study was 150 youth voters. Purposive sampling technique have been used with questionnaire as the instruments for collecting data. In determining the relationship between the voting refusal behaviors, Correlation Analysis and Regression Analysis were used. Based on the findings, ignorant is the main antecedent of youth refusal to vote in election. Hence, the government, political parties Election Commission of Malaysia and all beneficiaries must work together to ensure our youth exposed to political system and encourage them to involve in selecting the leaders.Â Â Â